PENGGUNAAN METODE STORYTELLING MELALUI CERITA RAKYAT DALAM MENANAMKAN NILAI KARAKTER SISWA SEKOLAH DASAR - Zuhriyah, Nurul Aisah Lailatuz; Fradana, Ahmad Nurefendi (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to explore the use of the storytelling method through folktales in instilling character values among elementary school students. A descriptive qualitative approach was employed, involving classroom teachers and fourth-grade students at SD Muhammadiyah 1 Krian, Sidoarjo Regency. Data were collected through in-depth interviews, classroom observations, and visual documentation. The findings indicate that the storytelling method not only enhances students’ imagination but also effectively instills character values such as honesty, responsibility, empathy, and respect for parents. Storytelling enables students to understand life values in a contextual and engaging manner while fostering emotional involvement in the learning process. Using folktales as learning material also strengthens students’ cultural identity and connects local wisdom with their personal experiences. Although challenges were found, such as varying student interests and limited locally relevant stories, teachers managed these through creative and adaptive approaches. Therefore, the storytelling method using folktales is proven to be an effective medium for character education at the elementary school level.